The Influence of STAD Model Assisted with ALPIN Media towards the Understanding of Students’ Concepts - Rizqa Aulia Rahmah; Fina Fakhriyah; Much. Arsyad Fardani (Jurnal Ilmiah Sekolah Dasar, 2020)
Lack of understanding of the concept has an impact on the low value of student scores in Indonesian language and natural science content. The purpose of this study was to examine the differences in the average ability of students' understanding of concepts between before and after the STAD learning model-assisted ALPIN media and measure the increase in students' understanding of concepts after being taught using the STAD learning model-assisted ALPIN media. This research is a quantitative study with a Pre-Experimental Design in the form of The One-Group Pretest-Posttest Design. The population in this study was a student of class IV SD. Sampling is done by a saturated sampling technique. The sample in this study was class IV SD, which amounted to 29 students. Data collection techniques in this study include observation, interviews, documentation, and tests. The data analysis technique used in processing research data is the normality test as a prerequisite test. In testing the research hypotheses used were paired sample t-test, N-gain test. The results showed that there were differences in the average ability of students' understanding of concepts after applying the Student Teams Achievement Division learning model-assisted ALPIN media, there is an increase in the ability to understand the concepts of students after using the STAD learning model-assisted ALPIN media.